Analysis of Economic Growths and Development Gaps Between Cities in Southeast Sulawesi - Muthalib, Abd Azis (International Journal of Economics and Financial Issues, 2017)
This study was conducted in the province of Southeast Sulawesi and aimed at finding out and analysing: (1) the level of economic growth of cities and regencies in Southeast Sulawesi; (2) development gaps between cities in the province; (3) the correlation between economic growth and development gaps between one city and the other. To determine the level of economic growth, a percentage method was used. To find out the level of development gap between regencies and cities Williamsom index was employed. To identify the relationship between level of economic growth and development gap between the cities, a coefficient correlation was used. Results of the study show that: (1) the economic growth in the cities and regencies within the province of Southeast Sulawesi over the period of 2010-2015 was between 6.68% and 12.04% per year. This figure was above our national economic growth, which was below 6% annually over the same period; (2) development gaps between one region and the other in Southeast Sulawesi were very narrow and relatively the same among the cities and regencies; (3) the economic growth had a positive, weak correlation with the development gaps, meaning that the higher the economic growth, the wider the gap. Keywords: Economic growth, Development gaps JEL Classifications: O11, O47